2023
DOI: 10.1063/5.0151559
|View full text |Cite
|
Sign up to set email alerts
|

NASICON-based all-solid-state Na–ion batteries: A perspective on manufacturing via tape-casting process

Abstract: On the background of the urgent demand to realize a decarbonized society, energy storage technology plays a key role in shifting from social activities founded on the combustion of fossil fuels to those based on renewable energy resources. Toward this end, global deployment of large-scale rechargeable batteries supplying electricity to power grids is imperative, which requires widespread commercialization of high-performance and safe batteries at a low price relying on abundant and ubiquitous source materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 375 publications
0
2
0
Order By: Relevance
“…25 Hasegawa et al reported NASICON-based solid electrolytes focusing on tape-casting processes and glass additives. 26 Oh et al fabricated a thin solid-state electrolyte with 86 μm thickness via tape-casting to reduce the internal resistance and enhance the energy density. 27 However, these wet processes suffer from several disadvantages, such as the requirement of hazardous organic materials, difficulties in controlling the particle shape-based agglomeration, and challenges associated with the producing of high-density sheets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Hasegawa et al reported NASICON-based solid electrolytes focusing on tape-casting processes and glass additives. 26 Oh et al fabricated a thin solid-state electrolyte with 86 μm thickness via tape-casting to reduce the internal resistance and enhance the energy density. 27 However, these wet processes suffer from several disadvantages, such as the requirement of hazardous organic materials, difficulties in controlling the particle shape-based agglomeration, and challenges associated with the producing of high-density sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Naranjo-Balseca et al obtained high-performance NASICON ceramic electrolytes via tape-casting, which exhibited a 0.1 mS cm –1 ionic conductivity at 20 °C . Hasegawa et al reported NASICON-based solid electrolytes focusing on tape-casting processes and glass additives . Oh et al.…”
Section: Introductionmentioning
confidence: 99%